Strengthening health-system emergency preparedness : toolkit for assessing health-system capacity for crisis management - World Health Organization. Regional Office for Europe (Denmark : WHO Regional Office for Europe, 2012)
Content: Part 1. user manual -- part 2. assessment form
Keywords: Delivery of Health Care -- organization and administration; Emergencies; Disasters; National Health Programs; Disease Outbreaks; Disaster Planning; Program Evaluation